Mucormycosis/ Zygomycosis: current concern - Modesto dos Santos, Vitorino (Revista de Medicina e Saúde de Brasília, 2016)
<span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Mucormycosis/ Zygomycosis is a rare invasive infection, mainly affecting immunocompromised hosts, and caused by filamentous fungi of Mucorales or Entomorphorales orders, which include the agents Mucorales spp, Mucor spp, Rhizopus spp, Rhizomucor spp, Cunninghamella, and Lichthemia corymbifera. The main predisposing factors are hematologic or solid malignancies and diabetes. Recent studies have confirmed that this uncommon infectious disease is mortal in about 50% of cases. Studies by Turkish and Australian authors and a Brazilian case report are commented.